2010
DOI: 10.1099/ijs.0.013979-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships within the family Halomonadaceae based on comparative 23S and 16S rRNA gene sequence analysis

Abstract: A phylogenetic study of the family Halomonadaceae was carried out based on complete 16S rRNA and 23S rRNA gene sequences. Several 16S rRNA genes of type strains were resequenced, and 28 new sequences of the 23S rRNA gene were obtained. Currently, the family includes nine genera (Carnimonas, Chromohalobacter, Cobetia, Halomonas, Halotalea, Kushneria, Modicisalibacter, Salinicola and Zymobacter). These genera are phylogenetically coherent except Halomonas, which is polyphyletic. This genus comprises two clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 72 publications
4
32
0
Order By: Relevance
“…Halomonas isolates were retrieved from all sample types, assigned to 7 distinct species and clustered within 3 phylogenetic groups: (i) Halomonas group I including H. ventosae ( n = 3), and H. taeanensis ( n = 3); (ii) Halomonas group II represented by H. elongata ( n = 4); and (iii) Halomonas group III constituted by H. boliviensis ( n = 2), H. gomseomensis ( n = 2) and the related species H. janggokensis ( n = 14) and H. subterranea ( n = 1) (Table 1, Figure 2). Considering the nonmonophyletic status of the Halomonas genus and the need of a deep taxonomic revision [65], the number of recovered species indicates high intragenus diversity. In addition, there was no clear correlation between the recovered Halomonas species with their isolation origin, pointing out their adaptation capabilities to harsh conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Halomonas isolates were retrieved from all sample types, assigned to 7 distinct species and clustered within 3 phylogenetic groups: (i) Halomonas group I including H. ventosae ( n = 3), and H. taeanensis ( n = 3); (ii) Halomonas group II represented by H. elongata ( n = 4); and (iii) Halomonas group III constituted by H. boliviensis ( n = 2), H. gomseomensis ( n = 2) and the related species H. janggokensis ( n = 14) and H. subterranea ( n = 1) (Table 1, Figure 2). Considering the nonmonophyletic status of the Halomonas genus and the need of a deep taxonomic revision [65], the number of recovered species indicates high intragenus diversity. In addition, there was no clear correlation between the recovered Halomonas species with their isolation origin, pointing out their adaptation capabilities to harsh conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Within this genus, Halomonas group III includes the 3 closely related species with 6 distinct ITS haplotypes: H. gomseomensis (H7 and H40) , H. janggokensis (H2, H9, and H22) and H. subterranea (H30). Isolates of these species that could be considered as a single one [65, 72] were recovered from all the sites except from Sabkhet El Melah (Table 1, Figure 3). Their high level of microdiversity could contribute to their ecological fitness and their ability to adapt to desert and saline environments.…”
Section: Resultsmentioning
confidence: 99%
“…Halomonas aquamarina , also in the Gammaproteobacteria, has been described as a slight-to-moderate halophile that produces ectoine as the principle compatible solute and has been isolated from many marine environments including the Pacific Ocean, deep-sea basins, Antarctica, and hypersaline lakes [37,38]. The genus Halomonas has a polyphyletic evolutionary lineage and contains at least 3 main evolutionary branches [38,39]. This may explain, in part, it wide ranging distribution.…”
Section: Discussionmentioning
confidence: 99%
“… S. socius SMB35 T (DSM 19940 T ) is the type strain of this species with a well-defined status within the family Halomonadaceae [9, 10], but the taxonomic placement of strains MH3R3–1 and SMB17 was not characterized in details. We compared partial (1333 bp) 16S rDNA sequences of MH3R3–1 and SMB17 to those of type strains ( n  = 53) representing main phylogenetic groups recognized within the family Halomonadaceae [10, 11].…”
Section: Organism Informationmentioning
confidence: 99%
“…We compared partial (1333 bp) 16S rDNA sequences of MH3R3–1 and SMB17 to those of type strains ( n  = 53) representing main phylogenetic groups recognized within the family Halomonadaceae [10, 11]. Results of the analysis revealed that the strain SMB17 belonged to the genus Chromohalobacter and was closely related to C. japonicus , whereas MH3R3–1 was most similar to Salinicola salarius and S. socius (Fig.…”
Section: Organism Informationmentioning
confidence: 99%